Sociodemographic profile of transsexual patients - Duišin, Dragana (Array, 2009)
Gender identity disorder is a rare entity in psychiatry which affects deep instincts and personal identity. A review of the recent literature has shown that research of socio-demographic characteristics of transsexual patients is sporadic. There are very few investigations which consider the socio-demographic characteristics in individuals with disharmonized sex and gender identity. This kind of research has not been done in Serbia until now. The objective of this research was to evaluate and analyze socio-demographic data of transsexual persons with a homosexual orientation. Subject and methods: The paper presents the mentioned characteristics on sample of 30 gender dysphoric persons. The patients were examined by The Belgrade team for gender identity. The transsexuals were in a stage of preparation for the sex reassignment surgery (SRS), and transsexualism was diagnosed and analyze socio-demographic data of transsexual persons with a homosexual orientation